Human Herpesviruses, Bacteria, and Fungi in Gingivitis and Periodontitis Pediatric Subjects: A Systematic Review - Federica Di Spirito; Massimo Pisano; Mario Caggiano; Giuseppina De Benedetto; Maria Pia Di Palo; Gianluigi Franci; Massimo Amato (Children)
Objectives: This systematic review assesses and compares the presence and relative abundance of periodontal pathogens, human herpesviruses (HHVs), and fungi in subgingival and/or saliva samples from pediatric subjects (≤18 years of age) with periodontally healthy status and with gingivitis and/or periodontitis. Methods: The study protocol was conducted under the PRISMA statement and registered on PROSPERO (CRD42024593007). Data from seven studies were descriptively analyzed and qualitatively assessed through the ROBINS-1 and JBI tools. Results: Pediatric subjects with clinically healthy periodontium exhibited a balanced microbiome, with early colonizers (Streptococcus species) supporting biofilm development and late colonizers like Fusobacterium nucleatum, Treponema denticola (82.35%), and Porphyromonas gingivalis (29.7%) present at low levels, suggesting subclinical dysbiosis. Viruses such as HSV-I (100%), CMV (17.8%), and EBV-I (22.09%) coexisted in a likely latent state, maintained by effective immune responses. In pediatric periodontitis, biofilms were more diverse and pathogenic, with increased prevalence of A. actinomycetemcomitans (56.09%), P. gingivalis (55.4%), and T. forsythia (35.9%). Generalized periodontitis showed higher CMV (36.36%) and EBV-I (36.24%) prevalence than gingivitis (HSV-I 18.75%). Coinfections were frequent in periodontitis, suggesting bacterial–viral synergy in exacerbating inflammation and tissue destruction. Fungi, although not studied, may also contribute under specific conditions. Conclusions: These findings highlight the role of microbial interactions in periodontal health and disease progression.